ASSESSING THE IMPLICATIONS OF K ISOTOPE COSMOCHEMISTRY FOR EVAPORATION IN THE PREPLANETARY SOLAR NEBULA - Young E.D. (My University, 2000)
Homogeneity in 41K/39K among Earth, Moon, chondrites, and achondrites has been cited as evidence that evaporation of protoplanetary dust could not have caused variability in the mass of moderately volatile elements among Solar System planets and meteorite parent bodies. Herein, consideration of a simple physical model for evaporation of mineral grains with finite K diffusivities shows that measured 41K/39K do not preclude extensive mass loss by evaporation of solid mineral grains in the preplanetary nebula. Instead the data constrain the grain size, temperature, and duration attending grain evaporation through the effects that these factors have on the evaporative-diffusive Peclet number. It is proposed that evaporation of solid dust comprising the precursors to planets can not be ruled out as a first-order mechanism for controlling the elemental composition of the rocky planets and asteroids.
Keywords: POTASSIUM; ISOTOPES; EARLY SOLAR NEBULA; MINERAL EVAPORATION